2005
DOI: 10.4141/p03-182
|View full text |Cite
|
Sign up to set email alerts
|

Soil and fertilizer phosphorus: Effects on plant P supply and mycorrhizal development

Abstract: . 2005. Soil and fertilizer phosphorus: Effects on plant P supply and mycorrhizal development. Can. J. Plant Sci. 85: 3-14. Plants require adequate P from the very early stages of growth for optimum crop production. Phosphorus supply to the crop is affected by soil P, P fertilizer management and by soil and environmental conditions influencing P phytoavailability and root growth. Phosphorus uptake in many crops is improved by associations with arbuscular mycorrhizal fungi. Cropping system and long-term input o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
139
1
14

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 262 publications
(165 citation statements)
references
References 93 publications
11
139
1
14
Order By: Relevance
“…Phosphorus is known for its functions on root formation in plants [13,34,35]. The improved uptake of different micronutrients in different plant tissues in this study, might have been caused by the possibility of increased root system which explored the bulk of soil for water and other mineral nutrients uptake which comes in contact with the roots [36]. However, the data from this study (Tables 2-5) showed that phosphorus supplementation either did not show significant difference (shoot) or significantly decreased the uptake of Zn and Fe in different plant organs tested.…”
Section: Discussionmentioning
confidence: 75%
“…Phosphorus is known for its functions on root formation in plants [13,34,35]. The improved uptake of different micronutrients in different plant tissues in this study, might have been caused by the possibility of increased root system which explored the bulk of soil for water and other mineral nutrients uptake which comes in contact with the roots [36]. However, the data from this study (Tables 2-5) showed that phosphorus supplementation either did not show significant difference (shoot) or significantly decreased the uptake of Zn and Fe in different plant organs tested.…”
Section: Discussionmentioning
confidence: 75%
“…Spring wheat (Triticium aestivum L.) and canola (Brassica napus L.) are major crops in western Canada. Spring wheat readily forms mycorrhizal associations while canola does not (Grant et al 2005). Therefore, tillage system may have different effects on P dynamics in canola than in spring wheat, due the effects of tillage on mycorrhizal association.…”
mentioning
confidence: 99%
“…Therefore, mycorrhizal activity and hence P supply may be influenced by both crop sequence and tillage system. Flax is more reliant on mycorrhizal associations than are spring wheat or canola (Grant et al 2005). Increasing mycorrhizal association in flax, through RT or sequencing flax after a mycorrhizal crop, may improve early-season P status of the crop and reduce the reliance on P fertilization.…”
mentioning
confidence: 99%
“…This shows that in the certain value of P concentration AMF would increase, but in the more value of P concentration, it could reduce AMF. Grant et al (2005) supported this statement and stated that AMF symbiosis decreased with increasing tissue P concentration. Therefore in the high P level in the soil, probably it could increase or decrease AMF association depending on the certain quantity of P concentration.…”
Section: Resultsmentioning
confidence: 71%